1998
DOI: 10.1002/(sici)1097-4644(19980301)68:3<287::aid-jcb1>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of in vitro mineralization from rabbit aorta and their role in biomineralization

Abstract: Mineralization of aorta is known to occur late in life and appears to be a pathological phenomenon. In vitro studies revealed that the matrix prepared from the thoracic aorta pieces after their extraction with 3% Na2HPO4 and 0.1 mM CaCl2 were mineralized under physiological conditions of temperature, pH, and ionic strength of the media to form matrix-bound mineral phase resembling hydroxyapatite in nature. However, the matrix identically prepared from the unextracted rabbits aortae failed to mineralize under i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Proteins present in the organic matrix of renal stones have been proposed to play an important role in kidney stone disease for several decades [36], [37]. Identification of proteins was hampered in the past by limitations in protein identification methods thereby making the identification of novel proteins quite difficult without prior knowledge of their involvement in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins present in the organic matrix of renal stones have been proposed to play an important role in kidney stone disease for several decades [36], [37]. Identification of proteins was hampered in the past by limitations in protein identification methods thereby making the identification of novel proteins quite difficult without prior knowledge of their involvement in this process.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,23 Adding the tendon extracts (obtained during preparation of extracted tendons) in the calcium and phosphate homogenous system can also inhibit precipitation of calcium and phosphate ions as a mineral phase. 12 Based on previous studies, two hypotheses could explain calcification produced by Na 2 HPO 4 extraction: 1) Na 2 HPO 4 specifically promotes dissociation from the tissue of a substance that inhibits calcification in situ; and 2) phosphate residuals alone, or in combination with endogenous Ca 2þ , bind at appropriate matrix sites, thus providing centers for nucleation and growth of calcium phosphate crystals. 10,11,13 The indentation test was used to evaluate mechanical properties of tendon in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] This theory is supported by data showing that tendon extraction with 3% Na 2 HPO 4 leads to a quick mineralization and re-adding the extract significantly inhibits the rates of calcium and phosphate uptake from the soluble phase. [11][12][13] However, a recent study showed that when the Na 2 HPO 4 -extracted tendon was incubated in a solution containing both calcium and phosphate, the mineralization process only lasted for several hours. 12 A decline in free calcium occurred quickly because of the spontaneous formation of apatite crystals in solution containing increased levels of calcium and phosphate.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The interaction between calcium and acidic Asp, Glu and Gla is certainly plausible, but it is equally conceivable that basic residues that are normally protonated at urinary pH and positively charged might experience an attraction toward negatively charged oxalate groups [27]. This is corroborated by the presence of basic amino acids too in the inhibitory proteins [28]. In either case steric constraints from 3D conformation of the molecule might limit the number of these simple interactions [27].…”
Section: Discussionmentioning
confidence: 99%